HUBUNGAN BUDAYA KERJA DENGAN BURNOUT PERAWAT DI RUANG RAWAT INAP RSUP DR. SITANALA TANGERANG - Ririn Alfiah Rianti (2021)
Burnout conditions in nurses to be unable to carry out their duties properly so that it affects in providing health services to patients. In providing health services, it must be in accordance with the work culture applied in the hospital. This research aims to analyze the relationship between Work Culture and Nurse Burnout. The study used a Cross Sectional research design with Chi Square and Spearman statistical tests with CI 95% that used Total Sampling technique of 39 nurses at RSUP.Dr. Sitanala Tangerang. The results showed 59.0% of nurses experienced Burnout, but no significant relationship was found between the Work Culture (P Value = 0.755) 95% CI with Nurse Burnout. The burnout rate for nurses should be suppressed through the application of a good work culture and for nurses who have a high hard work nature can be given rewards as a form of aspiration in accordance with their achievements in work